A genetically engineered therapeutic lectin inhibits human influenza A virus infection and sustains robust virus-specific CD8 T cell expansion. - Meng Yu; Ang Lin; Faezzah Baharom; Shuijie Li; Maureen Legendre; Evelyn Covés-Datson; Ebba Sohlberg; Susanne Schlisio; Karin Loré; David M Markovitz; Anna Smed-Sörensen (PLoS Pathogens)
Seasonal influenza continues to be a global health problem. Current existing vaccines and antivirals against influenza have limited effectiveness, and typically do not stay ahead of the viral evolutionary curve. Broad-spectrum antiviral agents that are effective therapeutically and prophylactically are much needed. We have created a promising new broad-spectrum anti-influenza agent using molecular engineering of a lectin from bananas, H84T, which is well-tolerated and protective in small animal models. However, the potency and effect of H84T on human immune cells and influenza-specific immune responses are undetermined. We found that H84T efficiently inhibited influenza A virus (IAV) replication in primary human dendritic cells (DCs) isolated from blood and tonsil, preserved DC viability and allowed acquisition and presentation of viral antigen. Excitingly, H84T-treated DCs subsequently initiated effective expansion of IAV-specific CD8 T cells. Furthermore, H84T preserved the capacity of IAV-exposed DCs to present a second non-IAV antigen and induce robust antigen-specific CD8 T cell expansion. Our data support H84T as a potent antiviral in humans as it not only effectively inhibits IAV infection, but also preserves induction of robust pathogen-specific adaptive immune responses against diverse antigens, which likely is clinically beneficial.